Partial penile amputation using a thoracoabdominal stapler in nine dogs. Issue 2 (11th February 2022) - Patel, Nikesh; Jones, Stephen C.; McLoughlin, Mary A.; Howard, James
Abstract: Objectives: To describe a novel technique for partial anatomic penile amputation using a thoracoabdominal stapler in dogs and to report any associated short‐term peri‐operative complications and clinical outcomes associated with the procedure. Materials and methods: Medical records from a tertiary referral hospital were reviewed for dogs undergoing penile amputation and scrotal urethrostomy between October 2007 and December 2019. Data collected included patient signalment, clinical signs on presentation, indication for penile amputation, surgical technique, duration of surgery, post‐operative complications, and short‐term outcome. Results: Nine dogs were included in the study. Indications for surgery were for treatment of chronic paraphimosis and priapism ( n = 3), recurrent urethral prolapse ( n = 2), balanoposthitis ( n = 1), masses arising from the penis, prepuce, and/or urethra ( n = 2), and penile trauma ( n = 1). All dogs underwent a scrotal urethrostomy followed by a partial penile amputation with a thoracoabdominal stapler. All dogs suffered mild post‐operative haemorrhage from the urethrostomy stoma. On recovery from general anaesthesia, 2/9 dogs were painful and another 2/9 dogs were dysphoric. Two dogs experienced incisional complications with mild swelling around the urethrostomy stoma. One dog experienced an infection of the penile amputation site 21 days after surgery. The short‐term outcomes for this procedure were excellent in 8/9 dogs. These outcomes were based on owner assessment of comfort and monitoring throughout the recovery period, manual palpation of the surgical site at the time re‐evaluation, and surgeon visualization of successful voluntary urination 14–35 days after surgery. Clinical significance: Use of a thoracoabdominal stapler is effective in achieving partial anatomic penile amputation in dogs. Abstract : The objective of this study was to describe a complete penile amputation technique using a thoracoabdominal stapler in dogs. The use of a thoracoabdominal stapler is an effective and efficient technique to achieve partial penile amputation in dogs in small animal practice.